Dynamic modelling and vibration simulation of air bearing spindle systems due to unbalance. (2017) - Cao, Hongrui; Riemer, Oltmann; Brinksmeier, Ekkard
Air bearing spindles are popularly used in ultra-precision machining, however, any slight mass unbalance in spindles can induce vibrations which may result in dimensional errors or poor surface finish of fabricated parts. In this paper, a complete dynamic model is proposed for air bearing spindle systems including air bearings, shaft, housing, and joint connections with the machine tool structure. The model is validated with experiments, and then vibration responses due to different types of unbalance are simulated quantitatively to reveal the characteristics of unbalance-induced vibrations. The results can provide proofs for the position selection of balancing planes as well as measurement points in automatic balancing process of air bearing spindles.